Competitive ligand exchange between Cu–humic acid complexes and methanobactin. Issue 1 (22nd October 2012) - Pesch, M.‐L.; Hoffmann, M.; Christl, I.; Kraemer, S. M.; Kretzschmar, R.
Abstract Copper has been found to play a key role in the physiology of methanotrophic micro‐organisms, and methane oxidation may critically depend on the availability of Cu. In natural environments, such as soils, sediments, peat bogs, and surface waters, the presence of natural organic matter (NOM) can control the bioavailability of Cu by forming strong metal complexes. To promote Cu acquisition, methanotrophs exude methanobactin, a ligand known to have a high affinity for Cu. In this study, the capability of methanobactin for Cu acquisition from NOM was investigated using humic acid (HA) as a model substance. The kinetics of ligand exchange between Cu–HA and methanobactin was observed by UV–vis spectroscopy, and the speciation of Cu bound to methanobactin was determined by size‐exclusion chromatography coupled to an ICP‐MS. The results showed that Cu was mobilized from HA by a fast ligand exchange reaction following a second‐order rate law with first‐order kinetics for both methanobactin and Cu–HA complexes. The reaction rates decreased with decreasing temperature. Equilibrium experiments indicated that methanobactin was not sorbed to HA and proved that methanobactin is competitive with HA for Cu binding by forming strong 1:1 Cu–methanobactin complexes. Consequently, our results demonstrate that methanobactin can efficiently acquire Cu in organic‐rich environments.